2010
DOI: 10.1063/1.3492714
|View full text |Cite
|
Sign up to set email alerts
|

Backward Raman compression of x-rays in metals and warm dense matters

Abstract: Experimentally observed decay rate of the long wavelength Langmuir wave in metals and dense plasmas is orders of magnitude larger than the prediction of the prevalent Landau damping theory. The discrepancy is explored, and the existence of a regime where the forward Raman scattering is stable and the backward Raman scattering is unstable is examined. The amplification of an x-ray pulse in this regime, via the backward Raman compression, is computationally demonstrated, and the optimal pulse duration and intens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…The development of such a light source is under increased attention, due to recent advances in the inertial confinement fusion [4][5][6] and the free electron laser (FEL) [7][8][9][10]. In conventional FEL, an ultrarelativistic electron beam interacts with the periodically laid-out strong magnets (so-called the wiggler or the undulator) and subsequently emits coherent photons [11].…”
Section: Introductionmentioning
confidence: 99%
“…The development of such a light source is under increased attention, due to recent advances in the inertial confinement fusion [4][5][6] and the free electron laser (FEL) [7][8][9][10]. In conventional FEL, an ultrarelativistic electron beam interacts with the periodically laid-out strong magnets (so-called the wiggler or the undulator) and subsequently emits coherent photons [11].…”
Section: Introductionmentioning
confidence: 99%
“…We also have shown that the unstable Langmuir wave due to the two-stream instability can have the frequency as large as 1.7 ω pe , which is impossible in the classical plasmas. Theses findings in this paper can have major implications on the Backward Raman scattering [15][16][17][18][19][20][21][22] and the beam stopping by the dense background plasmas.…”
Section: Discussionmentioning
confidence: 96%
“…This may be particularly useful for modeling BRA of powerful optical pulses in ionized low-density solids, or for BRA of intense x-ray pulses in denser plasmas, such as at solid densities. 14,15 While many of the BRA features were described computationally in previous studies (see for instance, Refs. [16][17][18][19][20][21][22][23][24][25][26][27][28], it is only here that a simple computational model is employed to study the major physical processes that are associated specifically with the QBRA regime.…”
Section: Introductionmentioning
confidence: 98%